METTL14 modulates the progression and ferroptosis of colitis by regulating the stability of m6A-modified GPX4 - Yuhua Chen; Weicong Fan; Ying Lyu; Jingsheng Liao; Ying Zhou (European Journal of Medical Research, 2025)
Abstract Ulcerative colitis (UC) is non-specific inflammatory bowel disease. UC development and progression were closely associated with epigenetic modifications. Nevertheless, the specific relationship between N6-methyladenosine (m6A) modification at RNA transcription levels and UC pathogenesis remains unclear. We established UC cell models and mouse models through dextran sulfate sodium (DSS) induction. The expression levels of METTL14 were analyzed via qRT-PCR and western blot. In vitro functional experiments evaluated the effects of METTL14 overexpression on the viability of DSS-induced NCM460 cells and ferroptosis markers. Use of the m6A methylation detection kit, MeRIP-qPCR, and RNA stability experiments confirmed the molecular mechanism controlled by METTL14. In vivo experiments with inflammatory mice models elucidated the interaction between METTL14 and GPX4. Findings from this study indicated a notable reduction in m6A methyltransferase METTL14 expression in DSS-induced NCM460 cells and DSS-induced mice models. METTL14 overexpression effectively suppressed ferroptosis in DSS-induced NCM460 cells. In addition, METTL14 enhanced GPX4 mRNA stability through mediating m6A modification, and the interplay between METTL14 and GPX4 through m6A modification introduced innovative therapeutic approaches for UC management.